2020
DOI: 10.5455/medarh.2020.74.275-278
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Perfused Peripapillary Capillaries and Peripapillary Capillary Density Maps in Glaucoma Patients

Abstract: Introduction: Monitoring and diagnosing glaucoma until 2017 included funduscopy, IOP measurements, gonioscopy, pachymetry, as well as visual field tests, optical coherence tomography (OCT) and optical coherence tomography angiography (OCT-A). Radial peripapillary capillaries (RPC) can be observed by fluorescein angiography, as well as histologically - superficial and deep capillary layer. Aim: To correlate density of radial peripapillary capillary network (RPC) and reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In healthy subjects, the average RPC plexus density was positively correlated with the average thickness of the RNFL [ 21 , 22 ], indicating that the RPC plexus supplies the RNFL around the optic nerve head [ 23 ]. Prior studies have also reported decreases in RPC density in patients with glaucoma, Fuch's syndrome, and nonarteritic anterior ischemic optic neuropathy, all of which are characterized by visual field defects [ 24 26 ]. In some case reports, VKH disease with optic disc swelling was accompanied by anterior ischemic optic neuropathy (AION), resulting in a reduced RNFL thickness and visual field defects, but AION was not found in patients with VKH disease without optic disc swelling [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, the average RPC plexus density was positively correlated with the average thickness of the RNFL [ 21 , 22 ], indicating that the RPC plexus supplies the RNFL around the optic nerve head [ 23 ]. Prior studies have also reported decreases in RPC density in patients with glaucoma, Fuch's syndrome, and nonarteritic anterior ischemic optic neuropathy, all of which are characterized by visual field defects [ 24 26 ]. In some case reports, VKH disease with optic disc swelling was accompanied by anterior ischemic optic neuropathy (AION), resulting in a reduced RNFL thickness and visual field defects, but AION was not found in patients with VKH disease without optic disc swelling [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in radial peripapillary capillary plexus density and nerve fiber layer thinning have been characterized in patients with early stage of glaucoma [117,118]. Besides, it is more prominent in patients with glaucoma for more than ten years than in patients with glaucoma less than ten years [119]. However, whether the peripapillary capillary changes in patients with COVID-19 are reversible will be seen in further studies.…”
Section: Covid-19 Related Expected Long-term Effects On Eyementioning
confidence: 93%